A case report of metronidazole-induced encephalopathy in Bangladesh - Mahmud, Shahriar (International Journal of Advances in Medicine, 2023)
Metronidazole-induced encephalopathy (MIE) is a rare disorder that can be reversible but fatal if not recognized early. Here, the author presents a case of encephalopathy in a 36-year-old patient who took 500 mg of metronidazole three times daily for three weeks. The patient was classified as a probable MIE case on the Naranjo causality assessment scale. An interesting neuroimaging finding in this patient was an isolated dentate nucleus signal abnormality. Author aims to report reversible clinical and radiological features of MIE in this patient and compare them with documented cases in recent and old literature. Data from this case report may guide clinicians to make judicious considerations in the early detection of MIE and may influence future researchers to focus on identifying critical mechanisms of devastating adverse effects, predictability of neurotoxicity.